Impact of Covid-19 Pandemic on Impulse Purchase Behaviour among Women Shoppers of Mumbai - Nair, Priya; Seshanna, Sudarshan; Plamoottil, Sumi Sam (The journal of contemporary issues in business and government, 2022)
As global economies started to shut down to prevent the spread of the Covid-19 virus, this changed businesses and consumers and how the two entities interacted. Disruptions in the supply chain caused mass anxieties and people were reported to be hoarding essential supplies such as toilet papers, food, and grocery items (The Times of India, 27 May 2020). The contrary was observed in the long run and saving rates reportedly improved (Financial Express, 1 June 2020). Scientific investigations into the short- and long-term effects of the pandemic on consumer behaviour are the need of the hour. The present research aims to contribute to this growing body of scientific knowledge by studying the short-term effects of the pandemic on the impulsive buying tendency of women consumers of Mumbai, India. It investigates how the experience of living with social restrictions and uncertainties might have affected the impulsive buying tendencies of subject consumers and their consumption of secondary need items such as clothes, personal care items, and luxuries. The research also discusses the decision-making process of consumers when the subjects are on an impulsive buying streak.